Longitudinal Relationships Between Empathy and Bullying Among Boys and Girls: A Random Intercept Cross‐Lagged Panel Model Study - Devleeschouwer, Charlie; Galand, Benoit; Tolmatcheff, Chloe; Salmivalli, Christina (Wiley, 2025)
For decades, empathy has been hypothesized as a protective factor against bullying. However, this hypothesis is mainly supported by cross-sectional studies, while longitudinal research on bullying and empathy is still scarce. The present study aimed to fill this gap by conducting random-intercept cross-lagged panel models of the relations between cognitive and affective empathy and bullying behaviors across three-time points each separated by 5 months, separately for boys and girls. Results from 1228 elementary school students (52.92% boys; Mage = 10.19, SD = 1.13) indicated that the associations between bullying and empathy are different for boys and girls. For boys, cognitive and affective empathy are negatively associated with bullying at the between level. At the within level, the only significant cross-lagged path indicated that a positive deviation from the expected score of cognitive empathy at baseline predicted a positive deviation from the expected score in bullying behavior 5 months later. For girls, there were no associations between empathy and bullying at either the within- or between-level. This study calls for further clarification of the direction of the relation between bullying and empathy before incorporating it into prevention programs.